Núcleo central da amígdala e Núcleo parabraquial lateral no controle da ingestão de sódio - Andrade, Gláucia Maria Fabrício de (2009)
Previous studies have shown the importance of serotonergic GABAergic and aadrenergic mechanisms of the lateral parabraquial nucleus (LBPN) in the control of sodium intake. The importance of the central nucleus of the amygdala (CeA) for sodium intake induced by different protocols was also demonstrated. Considering the studies showing reciprocal connections between these two structures, the objective of the present study was to investigate if the increase of sodium and water intake produced by the blockade of serotonergic mechanism, or the activation of GABAergic receptors or α2-adrenoceptors in the LPBN would depend on the CeA integrity. Male Holtzman rats with bilateral CeA lesions and bilateral stainless steel cannulas implanted in the LPBN were used to study the possible involvement of the CeA: 1) in water and 0.3 M NaCl intake produced by injections of the diuretic furosemide (FURO) combined with the angiotensin converting enzyme inhibitor captopril (CAP) subcutaneously (sc); 2) in the increase of 0.3 M NaCl intake induced by the blockade of serotonergic mechanisms or activation of the α2-adrenoceptors of the LPBN in rats treated with FURO + CAP sc; 3) in 0.3 M NaCl intake induced by the activation of GABAergic receptorss of the LPBN in satiated and normovolemic rats. Additionally, the pharmacological blockade of the CeA neurons with bilateral injections of GABAA receptor agonist muscimol was performed in order to test if the effects of CeA electrolytic lesions after the blockade of the inhibitory mechanisms of the NPBL were due to destruction of CeA neurons or destruction of fibers of passage. CeA lesionedrats had a decrease in daily water intake in comparison to sham-lesioned rats during the whole period of test, while the reduction of daily 0.3 M sodium intake occurred after the eighth day of lesions. Animals with bilateral lesions of the CeA also showed a reduction in body weight when compared to sham lesioned-rats. Bilateral lesions of the CeA did not affect FURO+CAP induced-water (9.2 1.6 ml/2 h vs. sham lesion: 12.8 0.7 ml/2 h) and 0.3 M NaCl intake (6.5 3.5 ml/2 h vs. sham lesion: 5.2 0.9 ml/2 h). Bilateral lesions of the CeA (3 days) completely abolished the ingestion of water (0.1 0.05 ml/4 h vs. sham lesion: 8.2 3.5 ml/4 h) and 0.3 M NaCl (0.1 0.1 ml/4 h vs. sham lesion: 16.1 5.4 ml/4 h) induced by bilateral injections of muscimol (0.5 nmol/0.2 μl) into the LPBN in satiated rats. Bilateral lesions of the CeA (5 to 18 days) also abolished the increase in 0.3 M NaCl (11,7 2,8 ml/2 h e 11,7 2,8 ml/2 h vs. sham lesion: 31,5 4,2 ml/2 h e 18,3 ± 3,1 ml/2 h) and water intake (6,7 1,8 ml/2 h e 13,8 2,7 ml/2 h vs. sham lesion: 19,9 3,2 ml/2 h e 22,4 2,5 ml/2 h) produced respectively by bilateral injections of moxonidine (0.5 nmol/0.2 μl) or methysergide (4 μg/0.2 μl) into the LPBN in FURO + CAP treated-rats. Bilateral injections of muscimol (0.5 nmol) into the CeA abolished water (0.1 0.02 ml/4 h vs. saline: 8.8 3.2 ml/4 h) and 0.3 M NaCl intake (0.1 0.04 ml/4h vs. saline: 19.1 6.4 ml/4 h) induced by bilateral injections of muscimol (0.5 nmol/0.2 μl) in the NPBL in satiated animals. Bilateral injections of muscimol (0.25 nmol/0.2 μl) in the CeA abolished the increase of water (3.3 2.3 ml/2 h vs. saline: 26.4 6.7 ml/2 h) and 0.3 M NaCl intake (2.8 1.6 ml/2 h vs. saline: 29.7 7.2 ml/2 h) produced by the bilateral injections of moxonidine (0.5 nmol/0.2 μl) into the NPBL. The present results show that CeA is essential for sodium and water intake after the blockade of LPBN inhibitory mechanisms. The suggestion is that CeA facilitatory mechanisms for sodium intake might be activated after the blockade of LPBN inhibitory mechanisms which might drive rats to ingest sodium. Therefore, if LPBN inhibitory mechanisms were acting normally, they may limit sodium intake because they inhibit CeA facilitatory signals for sodium intake.